Pemanfaatan Limbah Bawang Merah Untuk Pembuatan Media Tanam Di Desa Jamberejo Kecamatan Kedungadem Kabupaten Bojonegoro - Aditia Dwi Lestari; Moch. Suberi; Latifah Anom (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
This study aims to find out how to use shallot waste for the manufacture of planting media in Jamberejo Village, Kedungadem District, Bojonegoro Regency. The type of research used in this research is qualitative research. The sample data source used is the snowball sampling technique. While the data collection techniques using observation, interviews, and documentation. For the analysis of the data that has been obtained will be analyzed qualitatively and described in descriptive form. The results showed that the shallot waste used for the manufacture of planting media was successful or could be used for all types of plants because a good planting medium must meet certain requirements such as not containing pests and diseases, being able to hold water, but also being able to remove or drain excess water, loose and fertile so that the roots can grow and develop. In addition to being used as a planting medium, onion waste can also be used as animal feed, but must go through a drying process for onion waste first.